2017
DOI: 10.1080/15384101.2017.1363943
|View full text |Cite
|
Sign up to set email alerts
|

LPS-induced inflammatory response triggers cell cycle reactivation in murine neuronal cells through retinoblastoma proteins induction

Abstract: Cell cycle reactivation in adult neurons is an early hallmark of neurodegeneration. The lipopolysaccharide (LPS) is a well-known pro-inflammatory factor that provokes neuronal cell death via glial cells activation. The retinoblastoma (RB) family includes RB1/p105, retinoblastoma-like 1 (RBL1/p107), and retinoblastomalike 2 (Rb2/p130). Several studies have indicated that RB proteins exhibit tumor suppressor activities, and play a central role in cell cycle regulation. In this study, we assessed LPS-mediated inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Cancer is defined by uncontrolled repeat of cell cycle in an immortal way. On the other side, despite a progressive neurodegeneration in AD brains, the neurons show a substantial increase in their cell cycle related kinases (McShea et al, 2007; Chao et al, 2008; Majd et al, 2008; Moh et al, 2011; D’Angelo et al, 2017). This augmented attempt of neurons to proliferate is believed to start the neurodegenerative events, although its underlying mechanisms is still controversial.…”
Section: The Inverse Association Between Alzheimer’s Disease and Cancermentioning
confidence: 99%
“…Cancer is defined by uncontrolled repeat of cell cycle in an immortal way. On the other side, despite a progressive neurodegeneration in AD brains, the neurons show a substantial increase in their cell cycle related kinases (McShea et al, 2007; Chao et al, 2008; Majd et al, 2008; Moh et al, 2011; D’Angelo et al, 2017). This augmented attempt of neurons to proliferate is believed to start the neurodegenerative events, although its underlying mechanisms is still controversial.…”
Section: The Inverse Association Between Alzheimer’s Disease and Cancermentioning
confidence: 99%
“…Retinoblastoma protein (pRB) has been shown to regulate glucose tolerance, mitogenesis, glutathione synthesis, and the expression of genes involved in central carbon metabolism [57]. Several studies have indicated that pRb proteins exhibit tumor suppressor activities, and play a central role in cell cycle regulation [58]. In fact, recent data [44] have shown that this protein, although owing to its role in the G1/S cell cycle checkpoint, participates in many other cellular functions, including, counterintuitively, negative regulation of apoptosis.…”
Section: Prb Detectionmentioning
confidence: 99%
“…Similarly, we found that different mitogenic signaling pathways were enriched for the interactome associated with differentiation enriched genes found in our analysis. Of note, the inflammatory response can be a key event to trigger the cell cycle of neurons mediated by glial activation [24].…”
Section: Resultsmentioning
confidence: 99%